2020
DOI: 10.1016/j.pmedr.2020.101208
|View full text |Cite
|
Sign up to set email alerts
|

Vape shop owners’/managers’ attitudes about CBD, THC, and marijuana legal markets

Abstract: Highlights Vape shop owners/managers perceive minimal risk and therapeutic benefits of CBD. They held diverse perspectives regarding marijuana retail and its potential impact. Some owners/merchants do not consider the CBD or THC markets in their business. Others indicated high levels of enthusiasm for the growing retail marijuana market.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 39 publications
(45 reference statements)
1
23
0
Order By: Relevance
“…The prevalence of CBD co-marketing in our analysis of online vape shops mirrors the findings reported from in-store surveillance of brick-and-mortar vape shops and phone surveys with owners and managers of these shops, with all data suggesting that ~40% of both online and traditional vape shops have expanded their product offerings to include CBD [ 21 , 22 , 23 ]. Our analyses suggests that product offerings were not limited to vaping-type CBD products, with 12 distinct product categories identified.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The prevalence of CBD co-marketing in our analysis of online vape shops mirrors the findings reported from in-store surveillance of brick-and-mortar vape shops and phone surveys with owners and managers of these shops, with all data suggesting that ~40% of both online and traditional vape shops have expanded their product offerings to include CBD [ 21 , 22 , 23 ]. Our analyses suggests that product offerings were not limited to vaping-type CBD products, with 12 distinct product categories identified.…”
Section: Discussionsupporting
confidence: 73%
“…Another in-store surveillance of vape shops across six metropolitan statistical areas (MSAs; Atlanta, Boston, Minneapolis, Oklahoma City, San Diego, and Seattle) conducted by Berg et al in 2018 identified that 43% of vape shops sold CBD e-liquids and 23% sold other CBD-containing products [ 22 ]. An additional phone-based survey of vape shop owners/managers across the same MSAs further substantiated this finding, with 44% of owners/managers reporting that their shops sold CBD e-liquids [ 23 ]. Notably, all current surveillance has been limited by its focus on brick-and-mortar retailers, which may not mirror the e-commerce marketplace.…”
Section: Introductionmentioning
confidence: 95%
“…These data from a 2021 survey of 60 vape and vape-and-smoke shop owners and managers in six US MSAs indicated that federal policies and COVID-19-related orders were perceived to be somewhat easy to understand and implement, despite prior findings indicating noncompliance [ 23 , 32 , 33 ], and current findings indicating limited knowledge of relevant state and/or local T21 and flavored e-cigarette sales restrictions. Moreover, in response to increasing restrictions on e-cigarettes, vape retailers are expanding their product offerings, particularly to CBD products (as noted previously [ 32 , 34 , 43 ]), and are also increasing their online marketing, which reflects a global trend toward online e-cigarette marketing and sales [ 4 , 5 ]. These findings are critical to informing future surveillance of the e-cigarette retail environment, consumer behavior, and regulatory compliance.…”
Section: Discussionmentioning
confidence: 99%
“…The parent study, detailed elsewhere [ 23 , 34 , 42 , 43 , 44 ], was approved by the Emory University Institutional Review Board. This study focuses on 6 MSAs (Atlanta, Georgia; Boston, Massachusetts; Minneapolis, Minnesota; Oklahoma City, Oklahoma; San Diego, California; Seattle, Washington), selected based on the differences in state policy and retail markets for tobacco and cannabis.…”
Section: Methodsmentioning
confidence: 99%
“…(2) Second, we examined the marketing of substitute products such as cannabidiol (CBD), which like e-liquid, can be consumed by vaping ( Grafinger et al, 2020 ; Wheeler et al, 2020 ). Besides CBD not being explicitly mentioned among the restricted products, one might expect vape retailers to pivot to CBD given its soaring popularity and increasing uptake ( Berg et al, 2020 ). In the U.S., interest in these products is rivaling interest in e-cigarettes and vape retailers have begun selling CBD products ( Leas et al, 2019 ; Gammon et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%